RANTAI DISTRIBUSI IKAN TANGKAP DI DESA POHUWATO TIMUR KECAMATAN MARISA KABUPATEN POHUWATO - Fatmawati Fatmawati (Agropolitan, 2016)
The aim of this research is to identify the distribution of fish caught in the village of East Pohuwato and to know the size of the margin earned on each level marketing agencies catching fish. Techniques analysis used in this research was descriptive analysis and marketing margins. Descriptive analysis techniques are used to describe the distribution patterns of fisheries commodities. Then, to determine the cost of marketing and marketing margins at the institutional level in marketing channels used cost analysis tools and marketing margin which consists of calculating the marketing margin, cost and marketing advantages. Analysis of the marketing margin, used to measure the benefits of each actor involved in the distribution of fish. Distribution chain of fish caught in the village of East Pohuwato there are two marketing channels are channels I) Fishermen Traders Retailers Consumers, channel II) Fishermen RetailersConsumer. Margin marketing of fish caught in the marketing chain I) for traders which is a type of tuna per kg 1.000, - Kite Rp.2.000, - mackerel Rp.2.000, - cob 1.000, - and tuna Rp.2.000, - and for merchants retailer which is a type of tuna per kg Rp.2.000, - kite Rp.3.000, - mackerel Rp.3.000, - cob Rp.2.000, - and Rp.3.000, -. While in the marketing chain II) to retailers, which is a type of tuna per kg Rp.3.000, - Kite 5,000, - malarel 5,000, - cob Rp.3.000, - and tuna 5,000, -.